1992
DOI: 10.2466/pr0.71.8.1064-1066
|View full text |Cite
|
Sign up to set email alerts
|

Existential Anxiety as Related to Conceptualization of Self and of Death, Denial of Death, and Religiosity

Abstract: 82 students completed a questionnaire which measured their existential anxiety as described by Yalom, conceptualization of self and of death, denial of death, and religiosity. For these students, scores on existential anxiety correlated with identity confusion, feeling responsible toward others but fearing emotional closeness with them, seeing people as fundamentally different and not seeing oneself as living on in one's tasks or projects. Their existential anxiety scores were not related to a particular conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Moreover, a significant relationship was found between the existential anxiety construct assessed by EAS and death denial. This finding agrees with the opinions of existential psychologists and the results of previous studies (Westman, 1992;Yalom, 1980). For example, it was entirely similar to Westman 's finding because both of them found a relationship between existential anxiety and death denial, not any other aspect of death and dying (Westman, 1992).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, a significant relationship was found between the existential anxiety construct assessed by EAS and death denial. This finding agrees with the opinions of existential psychologists and the results of previous studies (Westman, 1992;Yalom, 1980). For example, it was entirely similar to Westman 's finding because both of them found a relationship between existential anxiety and death denial, not any other aspect of death and dying (Westman, 1992).…”
Section: Discussionsupporting
confidence: 93%
“…This finding agrees with the opinions of existential psychologists and the results of previous studies (Westman, 1992;Yalom, 1980). For example, it was entirely similar to Westman 's finding because both of them found a relationship between existential anxiety and death denial, not any other aspect of death and dying (Westman, 1992). In addition, the results indicated a significant positive relationship between happiness assessed by OHI and death acceptance, which is similar to a previous study (Abdel-Khalek, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Each of the items assesses the respondent's beliefs about the meaning, significance and importance of their interests, activities, and life. Research on existential anxiety conceptualized in this manner has used primarily adult samples and has shown that concerns about meaning and emptiness are associated with a confused identity, a fear of emotional closeness, despair, the denial of death (Westman, 1992) and a defensive coping style (Bylski and Westman, 1991). Moreover, clinicians have been aware of the role of meaninglessness in negative emotional states such as depression (see Frankl, 1963;Beck 1976) and the process of therapy (Yalom, 1975) for some time.…”
Section: Emptiness and Meaninglessnessmentioning
confidence: 99%
“…Westman (1992) used the EAS in a study with 82 students, and correlated it with the Denial Questionnaire and the Conceptualization of Self and of Death Questionnaire. She found expected correlations with identity diffusion, despair about life, denial of death and less extension into tasks, but not with conceptualization of death, religiosity, egocentricity, and irresponsibility.…”
Section: Resultsmentioning
confidence: 99%